2014
DOI: 10.1007/s12028-014-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin for Control of ICP

Abstract: non-English, retrospective studies, no documentation of ICP response to indomethacin, and animal studies. A two-tier filter of references was conducted. First, we screened manuscripts by title and abstract. Second, those references passing the first filter were pulled, and the full manuscript was checked to see if it matched the criteria for inclusion. Two reviewers independently extracted data including population characteristics and treatment characteristics. The strength of evidence was adjudicated using bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Indomethacin may have some advantage due to its effect of reducing ICP. 50 Caution is required with potential side effects of NSAIDs, and gastric protection may be needed.…”
Section: Management Principlesmentioning
confidence: 99%
“…Indomethacin may have some advantage due to its effect of reducing ICP. 50 Caution is required with potential side effects of NSAIDs, and gastric protection may be needed.…”
Section: Management Principlesmentioning
confidence: 99%
“…We found no randomised studies conducted on this topic, but we did find a review that assessed the use of indomethacin and its e ects on intracranial pressure (ICP) in patients with neurological illness (Sader 2015). This review defined eligible studies as being prospective, with five or more participants who had a documented response to indomethacin, and with trial reports published in English.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…Sader 2015 stated that nine out of 10 studies documented a decrease in ICP with indomethacin administration, and concluded that evidence provided by these studies suggested that indomethacin may reduce ICP in the severe TBI population. However, studies which did not show an e ect of indomethacin on ICP were not eligible for inclusion in the review, so indomethacin for ICP control remains experimental and further prospective studies are needed (Sader 2015). Only two studies included in the Sader 2015 review reported adverse events related to indomethacin administration: one was a study of people with severe TBI, where there was a critical reduction in jugular venous oxygen saturation in two of the six patients treated with indomethacin; and the other was a study of idiopathic intracranial hypertension which described dizziness in four patients.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%